Causes of Hospitalization in Children with Down Syndrome - Takita, Stefanie Yaemi [UNESP]; Sé, Ana Beatriz Silva [UNESP]; Hoffmann, Giovanna Michelin [UNESP]; Bunduki, William [UNESP]; Carvalho, Lidia Raquel [UNESP]; Fonseca, Cátia Regina Branco [UNESP] (MDPI, 2024)
Background and Objectives: Down syndrome (DS) is the most common chromosomal disorder in the world. It is caused by the imbalance of the chromosomal constitution of 21 by free trisomy, translocation or mosaicism. Children and adolescents with Down syndrome have immune dysregulation and are more susceptible to infections. This study aims to evaluate hospitalizations of children and adolescents with DS in the pediatric ward of Botucatu Clinics Hospital (HCFMB) and to classify the population of children included in the study according to age, diagnosis, outpatient follow-up, length of stay and need for the intensive care unit (ICU). Thus, it will be possible to improve care for these children, aiming to reduce these hospitalizations. Materials and Methods: This study was an observational, cross-sectional study, with retrospective data collected from the last nine years of hospitalization, from January 2013 to December 2021, from children and adolescents with DS in the pediatric ward, emergency room, and the ICU of HCFMB. Children hospitalized in this period in the pediatric ward and ICU, in the age range of 30 days to 15 years, were included in this study. The evaluation of comorbidities that culminated in the need for hospitalization in this population can be the focus of actions to improve the diagnoses and conducts for this population, which can prevent worsening illness and hospitalizations in future populations. Results: In this analysis, 80 children with DS were evaluated, with a total of 283 hospitalizations. The most prevalent age group was 1 to 3 years, and the main cause was due to problems in the respiratory system (99 cases). Among the respiratory causes, the main cause of hospitalization was due to pneumonia in 50% of cases, followed by acute respiratory failure in 14%. The average hospitalization time was 8 days, and in 49 hospitalizations, the children required the ICU. The main cause of hospitalization in the ICU was due to respiratory causes (36%), followed by cardiac malformations (14%). During the ICU hospitalizations, there were 13 deaths, and we observed a higher prevalence of heart conditions and, in some cases, positive urine cultures in these children. Conclusions: The Hospital serves as a reference for pediatric hospitalizations within its region and beyond, owing to its specialized capabilities. The main causes of hospitalization were those related to the respiratory system and cardiac malformations. Roughly one-third of the children required admission to the intensive care unit.
Keywords: children; Down syndrome; health care; health evaluation; hospitalization; outcome assessment